2000
DOI: 10.2174/1389201003378870
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondriotropic Cationic Vesicles A Strategy Towards Mitochondrial Gene Therapy

Abstract: The number of diseases found to be associated with defects of the mitochondrial genome has grown significantly over the last decade. Despite major advances in understanding mtDNA defects at the genetic and biochemical level, there is no satisfactory treatment for the vast majority of patients available. This is largely due to the fact that almost all mitochondrial DNA defects involve the final common pathway of oxidative metabolism making it impossible to bypass the defect by giving alternative metabolic carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Electron microscopic images of DQAsome-DNA complexes, i.e. DQAplexes (27), strikingly resembled the "spaghetti-and-meatball" shapes observed earlier with lipoplexes (44). It was further demonstrated that DQAplexes containing DNA at a molar ratio of DQA/DNA 6:1 completely protect the DNA against DNAse activity (45), and as shown earlier for lipoplexes (46) the addition of negatively charged lipids also releases intact DNA from the DQAsome-DNA complex (45).…”
Section: Mitochondria-targeted Dna Deliverysupporting
confidence: 75%
See 1 more Smart Citation
“…Electron microscopic images of DQAsome-DNA complexes, i.e. DQAplexes (27), strikingly resembled the "spaghetti-and-meatball" shapes observed earlier with lipoplexes (44). It was further demonstrated that DQAplexes containing DNA at a molar ratio of DQA/DNA 6:1 completely protect the DNA against DNAse activity (45), and as shown earlier for lipoplexes (46) the addition of negatively charged lipids also releases intact DNA from the DQAsome-DNA complex (45).…”
Section: Mitochondria-targeted Dna Deliverysupporting
confidence: 75%
“…Therefore, the selfassociation properties of DQA were studied in more detail. Monte Carlo computer simulations applied to a system of DQA-like single-chain bola-form amphiphiles, in a coarsegrained model, revealed the formation of vesicles, micelles, cylinders, disks, and planar aggregates as well as the possible co-existence of horseshoe and stretched conformation, all depending on lipid concentration and temperature used in that model (27,28).…”
mentioning
confidence: 99%
“…The results are in perfect agreement with previously published data. 53 Oligreen dye-exclusion assays were performed The effects of 12-cyclohexyl-DQA gapmer nanocomplexes and equivalent empty bolasome treatments on the growth of log-phase C. difficile cultures were replicated and further measured using quantitative CFU counts in triplicate. CFU results are expressed as average CFU/mL growth normalized to initial inoculum CFU counts ( Figure 9).…”
Section: Characterization Of Cyclohexyl-dqa Bolasomesmentioning
confidence: 99%
“…Vitamin E, conjugated to TPP (a lipophilic triphenylphosphonium cation) was also delivered selectively to mitochondria (65). "Mitochondriotropics," a term proposed by Weissig and Torchilin to describe the ability of molecules to diffuse into the intramitochondrial sites, has been an interesting concept (66,67). According to this, the properties of each one of the proposed therapeutics for mitochondrial disorders can influence its "trafficking" towards specific mitochondrial sites and in a state to "deliver" its intended therapeutic action.…”
Section: Targeting Mitochondriamentioning
confidence: 99%